Does Economic Growth Lead to Government Expenditure in Indonesia? - Imantria, Benny (Terbuka Journal of Economics and Business, 2025)
Economic growth effect on government expenditure has been debated theoretically and empirically. This study aims to identify the unidirectional relationship from GDP and government revenue to government expenditure in the short and long-run in Indonesia. Data sample used is a time series from 1976 to 2023, analyzed using ARDL model. The novelties lie in the time period, data variables, and analytical methods. This study found that GDP has no effect in the short-run, but GDP has a significant positive effect on government expenditure in the long-run, indicating that wagner's law has occurred in Indonesia during the observation period. Government revenue has a significant effect on government expenditure in the short and long-run, although the magnitude effect is lower in the long-run. Therefore, government expenditure is mainly determined by government revenue in the short-run and GDP in the long-run. Policymakers are expected to increase economic growth and government revenue, as well as allocate and realize government expenditure effectively